Mineral processing at Luleå University of Technology : meeting the research and educational needs - Rosenkranz, Jan (Luleå tekniska universitet, Industriell miljö- och processteknik, 2010)
With the start of the new decade the Mineral Processing chair at Luleå University of Technology has been newly appointed. The scientific redirection of the chair includes several of the important topic areas of advanced mineral processing. From process mineralogy via comminution and concentration processes to mathematical modelling and simulation of particulate processing systems, the mineral processing research at Luleå University of Technology is shaped by the interaction of material, process and equipment. This contribution deals with the positioning of the chair in research and education to meet the upcoming needs in a time where the secured supply with high quality commodities is essential Godkänd; 2010; 20100429 (janros)